The Identification of Criteria and Indicators to Evaluate Hazardous Street Trees: A Delphi Study. - Maruthaveeran, Sreetheran (2002)
Trees have been playing an important roles in our lives for centuries, however too often we are unaware of the risk associated with the trees. Trees with defects may become hazard and cause personal injury or property damage. Structural defects such as decay. cavities, dead limbs, splits and shakes and injured roots, heavy horizontal limbs, wind and vehicle damage, leaning trees are some of the factors that predisposes a tree to failure such as property damage and personal injury. Interest in hazard tree management has increased in recent years due to safety and liability concerns. Recognizing hazardous trees and taking proper corrective actions can protect property and save lives. To achieve the initial step especially for the hazard tree management. a study was conducted to identify the criteria and indicators for evaluating and identifying hazardous street trees. The purpose of this study were: (1) to develop a reliable set of criteria for evaluating hazardous street in urban areas, (2) to develop a reliable set of indicators for evaluating hazardous street trees in urban areas and (3) to examine the relationship between group of experts in the Delphi process. Delphi method was used in this study to solicit the opinion from the expert. It is an iterative process for soliciting and collating opinions on a particular topic through a series of Questionnaire. Finally, this study has been successful in using the Delphi method that generated and identified six criteria and 38 indicators that need to evaluate and identify hazardous street trees. Besides developing the criteria and indicators, this study also indicated that there were no any differences in opinion between the lecturers and officers from the government agencies and even between respondents from different education levels. Hopefully the generated criteria and indicators will be an initial step for the Shade Tree Unit of DBKL to implement their hazard tree management programme.